Developing a Cell-Free Extract Reaction (CFER) System in Clostridium thermocellum to Identify Metabolic Limitations to Ethanol Production - Cui, Jingxuan; Stevenson, David; Korosh, Travis; Amador-Noguez, Daniel; Olson, Daniel G.; Lynd, Lee R. (Frontiers in Energy Research, 2020)
The cellulolytic bacterium Clostridium thermocellum is a promising candidate for lignocellulosic biofuel production; however, ethanol titer needs to be improved for commercialization. To understand the factors limiting ethanol titer in C. thermocellum, we developed a cell-free extract reaction (CFER) system. We demonstrated that 15 mM cellobiose could be converted, in vitro, to 25 mM ethanol and that this reaction functions both at thermophilic (55°C) and mesophilic (37°C) temperatures. Although the yield was similar to that produced by whole cells, the rate was much slower ( 0.5 vs. 12 mM/h). In order to reliably quantify metabolites, rapid CFER quenching is necessary. Among the methods tested, filtration with a 3-kDa molecular weight cutoff filter proved to be the most effective. Metabolomic analysis revealed high levels of glucose-6-phosphate (G6P) and fructose-6-phosphate (F6P) in the CFER, identifying potential rate-limiting enzymes downstream of F6P. NADH was also found to accumulate in the CFER, suggesting that NADH recycling is rate-limiting. We used two complementary strategies to identify enzymes that limit metabolic flux, including feeding different substrates and supplementing with exogenous enzymes. In the enzyme addition experiment, the largest improvement was observed with the addition of yeast alcohol dehydrogenase (ADH), indicating a limitation at that reaction. The development of a CFER system for C. thermocellum, combined with detailed measurements of intermediate metabolites, allowed us to directly observe the metabolism of this organism, and suggested several potential metabolic engineering interventions for increasing ethanol titer. This demonstrates a technique that may be of general use for metabolic engineering in non-model organisms.